A justiça restaurativa como política pública de educação: um estudo sobre as práticas restaurativas em escolas de São Caetano do Sul-SP. - Rezende, Liliane Claro de (2017)
The purpose of this study was to analyze the implementation of Restorative Justice as an educational public policy to solve conflicts, in the city of São Caetano do Sul, greater São Paulo, in 2005. Specific objectives were as follows: a) To identify what factors contributed (or contribute) to the continuation (or not) of the Program; b) To analyze the possible results achieved in the last 11 years, regarding the schools involved or studied in this research. The relevance of this research is because those restorative practices in the schools of São Caetano do Sul were pioneering actions that contributed to further implementation of this public policy in several other cities in the state of São Paulo in the following years. The methodology to collect data for this research included bibliographic research on the topic (Restorative Justice. Restorative Practices. Educational Public Policies. São Caetano do Sul City) as well as document research (based on Acts, Executive Orders, Resolutions, Ministerial Orders, official documents about the implementation and first results of restorative practices in the city of São Caetano do Sul). It can be determined that the project called ¿Justice and Education: a partnership for citizenship¿, implemented in São Caetano do Sul, in 2005, can be considered the foundation for the implementation of Restorative Justice in the Brazilian Educational System. As a pilot, the project had both positive results as well as aspects that needed to be reassessed, once they prevented the project to be fully implemented in all schools. Positive aspects comprised: a) the strengthening of the partnership between the Legal and Educational systems in the State of São Paulo; b) New restorative practices, with different frameworks, that emerged during the process and were adopted in São Caetano do Sul and other cities; c) New Agents of Change that stood out in many schools, and by bringing them to other schools in the State it helped to spread the concept of Restorative Justice and its applications in the Educational field; d) The pursue of the ideal of Restorative Justice in São Caetano do Sul and continuing training programs for educators; e) The network to ensure Rights of Children and Teenagers has been organized, implemented and is now in full use; f) The concept that Formal Education is a task that does not belong only to schools, but also to all institutions in a ¿territory¿ (the educational field) and involves the family, has been consolidated; g) systematization and external evaluation of projects called ¿Justice and Education¿ in the cities of São Caetano do Sul, Heliópolis and Guarulhos, have been recorded as books and become available online, which enabled the reproduction and multiplication of the Restorative Justice approach in many cities in the state of São Paulo and in other states in Brazil. Aspects that, according to other implementations, need to be reassessed: a) the need of a career plan for teachers who perform restorative circles; b) a wider dissemination of the principles of restorative justice within the community and the school environment, so that everyone can contribute for the construction of a more democratic society; c) close monitoring, by the governmental agencies, regarding training programs and monitoring projects in progress, besides d) continuous investment both financial and of personnel. Finally, it is possible to conclude that São Caetano do Sul has become an incubator for Restorative Justice in Brazil ¿ and its educational system. It is important to point out, though, that only through a more democratic school education will the wide and full implementation of Restorative Justice in Brazilian schools be possible.